Physiological and thermal response to real-life transient conditions during winter in severe cold area. (15th June 2019) - Chen, Xin; Xue, Puning; Gao, Lixin; Du, Jing; Liu, Jing
Abstract: Transient changes of thermal environment cause significant thermal stress in extreme climates. This study explores human physiological and thermal responses in severe cold area during winter. A questionnaire survey and a series of experiments were conducted in Harbin, a city that is situated in a part of China known for severe cold climatic conditions in some seasons. The survey was a preliminary part investigating human clothing habits during winter. Subsequent experiments were designed to reveal the effect of exposed body parts on physiological and thermal responses. When hands are exposed, symptoms appear earlier and more frequently. Hand exposure causes more local thermal sensation vote (TSV) changes, raises the TSV value corresponding to the most comfortable state, and intensifies discomfort in cold and uncomfortable environment. However, direct cooling of facial region induces effective thermoregulatory processes more easily indicated by nasal discharge, sneezing, and shivering. The overall TSV is closest to that of the coldest parts in the outdoor environment during winter. Overall thermal sensation is warmer under warm stimulation than cold stimulation at identical mean skin temperatures (MST). Dynamic thermal sensation are estimated by MST, MST change rate and temperature difference between hand and forearm, respectively. Our results confirm the importance of considering human local exposure in scientifically evaluating thermal comfort in severe cold climates, since different local exposure induces different levels of physiological and thermal response. Highlights: Real-life local body exposure types were defined in the preliminary field survey. Dynamic thermophysiological adjustments form indoor to outdoor were studied. Overall TSV was closest to that of the coldest parts in cold outdoor environment. Direct cooling of core body regions provoked thermoregulatory processes more easily. Participants felt warmer under warm stimulation at identical mean skin temperature.